Spatial and single cell mapping of castleman disease reveals key stromal cell types and cytokine pathways - David Smith; Anna Eichinger; Éanna Fennell; Zijun Y. Xu-Monette; Andrew Rech; Julia Wang; Eduardo Esteva; Arta Seyedian; Xiaoxu Yang; Mei Zhang; Dan Martinez; Kai Tan; et al. (Nature Communications)
Abstract To determine the cellular and molecular basis of Castleman Disease (CD), we analyze the spatial proteome and transcriptome from a discovery (n = 9 cases) and validation (n = 13 cases) cohort of Unicentric CD, idiopathic Multicentric CD, HHV8-associated MCD, and reactive lymph nodes. CD shows increased stromal cells that form unique microenvironments. Interaction of activated follicular dendritic cell (FDC) cytoplasmic meshworks with mantle-zone B cells is associated with B-cell activation and differentiation. CXCL13+ FDCs, PDGFRA + T-zone reticular cells (TRC), and ACTA2-positive perivascular reticular cells (PRC) were the predominant source of increased VEGF expression and IL-6 signaling. MCD is characterized by increased TRC while UCD shows increased B-reticular cells (BRC). VEGF expression by FDCs is associated with peri-follicular neovascularization. FDC, TRC and PRC of CD activates JAK-STAT, TGFβ, and MAPK pathways via specific ligand-receptor interactions. Here, we show that stromal-cell activation and associated B cell activation and differentiation, neovascularization and stromal remodeling underlie CD.